Learning about the Historical Building in Malacca Malay Sultanate Era Using Augmented Reality - Anis Syafiqah Rozaidi; Nadia Akma Ahmad Zaki; Achmad Yani (International Journal of Multimedia and Recent Innovation (IJMARI), 2023)
Travel to Melaka application used to learn about the historical building in Malacca Malay Sultanate Era by using Augmented Reality (AR) technology. Learn about the historical building is very important. However, there are some students who are bored and not interested in learning History subject. The purpose of this application is to develop an educational application based on Augmented Reality for students to interest them in learning about the historical building. The design of this application is developed using multimedia elements which may interest the students to use this application. This application development was developed using the ADDIE Model. In addition, this research was evaluated by among 35 students from Sultan Idris Education University who pursuing a Bachelor of Education (History) with Honors by using quantitative methods through online questionnaire. As a result of the questionnaire, majority of respondents gave positive feedback and interested with Travel to Melaka application. In conclusion, learning about historical building in Malacca Malay Sultanate Era using Augmented Reality provides better knowledge and understanding.